PENGARUH EFEKTIFITAS KEPEMIMPINAN LEADER MEMBER â EXCHANGE (LMX) DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP RESISTANCE TO CHANGE - , MURSITO WIMBO WIBOWO, Drs. Fathul Himam, M.Psi, MA, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the effect of leadership effectiveness Leader- Member Exchange and Organizational Citizenship Behavior on Resistance to Change in employee Abadi Hotel Yogyakarta. This study used a purposive sampling technique of sampling of 56 research subjects employees Abadi Hotel Yogyakarta. The research data were collected by using a multidimensional LMX scale and Organizational Citizenship Behavior scale, the scale of RTCS Based on the results of statistical analysis found the pattern of relationships as follows: (1) there is a significant negative effect between LMX Leadership with Resistance to Change (partial r -0327, p < 0,05) means that can minimize the effectiveness of LMX leadership Resistance to Change, the higher the quality LMX will subject the lower the weight of Resistance to Change the effective contribution of 10,7% (2) there is a significant negative effect between Organizational Citizenship Behavior perception with Resistance to Change (partial r -0,704, p < 0,05) Organizational Citizenship Behavior that is higher the lower the Resistance to Change, by weight 49,5% effective contribution.